2018
DOI: 10.1016/j.jcol.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal preparations for colonoscopy. Comparative study: mannitol, picosulphate and macrogol

Abstract: Bowel preparation is mandatory prior to elective colonoscopy and their effectiveness is closely related to the quality of the examination. There are many preparations on the market and there is no consensus on which is best. This study aimed to compare three solutions for colon preparation in patients undergoing colonoscopy. We conducted a prospective study with 61 patients divided randomly into three groups: one that received a standard dose of macrogol, another received a standard dose of 10% mannitol and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
8

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 11 publications
0
4
0
8
Order By: Relevance
“…On the other hand, the mean AUC 0–∞ in the case of the optimized formula containing mannitol (OFM) was not significantly different from the market product with a p -value of 0.230. This insignificant increase in the AUC values could be attributed to the possible reduction in the GIT transit time in the presence of mannitol which could counteract the increase in the drug dissolution rate [73,74]. It was previously reported that mannitol in small concentrations could reduce the bioavailability of drugs, especially those absorbed from the small intestine [75,76].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the mean AUC 0–∞ in the case of the optimized formula containing mannitol (OFM) was not significantly different from the market product with a p -value of 0.230. This insignificant increase in the AUC values could be attributed to the possible reduction in the GIT transit time in the presence of mannitol which could counteract the increase in the drug dissolution rate [73,74]. It was previously reported that mannitol in small concentrations could reduce the bioavailability of drugs, especially those absorbed from the small intestine [75,76].…”
Section: Resultsmentioning
confidence: 99%
“…Ao final, foram incluídos 23 estudos na metanálise (Quadro 1). Seis estudos comparam regimes de preparo no dia anterior (Regev et al, 1998;Katz et al, 2013;Kim et al, 2014a;Kojecky et al, 2018;Quaresma et al, 2018;Kojecky et al, 2019) enquanto dez estudos compararam regimes de preparo fracionado (Kim et al, 2014b;Leitao et al, 2014;Jeon et al, 2015;Kim et al, 2015;Munsterman et al, 2015;Yoo et al, 2015;Kojecky et al, 2018;Mathus-Vliegen et al, 2018;Seo et al, 2018;Kojecky et al, 2019). Nenhum dos estudos incluídos comparou regimes de preparo exclusivamente no mesmo dia.…”
Section: Resultados 41 Busca E Seleção Dos Estudosunclassified
“…O citrato de magnésio também foi utilizado separado do picossulfato de sódio em um estudo (Kao et al, 2011). resíduos, respectivamente, por mais um, dois, dois e três dias adicionais (Regev et al, 1998;Kao et al, 2011;Lawarence et al, 2011;Katz et al, 2013;Rex et al, 2013;Muñoz et al, 2018;Quaresma et al, 2018;Seo et al, 2018;Rostom et al, 2019). Os demais quatorze estudos fizeram uso de dietas com baixo teor de resíduos ou pobre em fibra por períodos que variaram de um a sete dia antes (Manes et al, 2013;Kang et al, 2014;Kim et al, 2014a;Kim et al, 2014b;Jeon et al, 2015;Kim et al, 2015;Leitao et al, 2014;Munsterman et al, 2015;Pohl et al, 2015;Yoo et al, 2015Kojecky et al, 2018Mathus-Vliegen et al, 2018;Pisera et al, 2018;Seo et al, 2018;Kojecky et al, 2019).…”
Section: Resultados 41 Busca E Seleção Dos Estudosunclassified
See 2 more Smart Citations